NEW WRITERS, NEW READERS, AND THE FORMATION OF MASS LITERATURE IN SOUTHERN VIETNAM IN THE LATE 19TH AND EARLY 20TH CENTURY - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The transition of Vietnamese literature from the traditional China-like paradigm to the modern Western paradigmfirst began in Southern Vietnam. As residents of a French colonial territory, Southern Vietnamesewere early exposed to Western culture and literature, which aided in the formation of mass literature herein. Because mass literature realistically reflects experiences and lives of ordinary people, itis an important source to gain insight into social reality and consciousness during the period. It is also worth noting that mass literature is neither a compilation of cultural consumption related values, nor is it a means of communication that has a significant influence on the public's thought, nor is it an anticultural entity. However, this literary tendency, especially in Southern Vietnam in the late 19th and early 20th century, has gone unnoticed in Vietnam for years. This paper studies the emergence of new generations of writers and readers, focusing on both their cultural, psychological, and intellectual foundations, and their significant roles in the formation of Vietnamese mass literature.